Health Impact of Tailpipe Emission: An Empirical Study with Reference to Central Development Region of Nepal - Khadka, Chakra Bahadur (Economic Journal of Development Issues, 2010)
The smoke that comes out from the use of petroleum product impacts the physical health of people by affecting the environment in which they live in because well-known toxin like carcinogens benzene and polyaromatic hydrocarbons are present in the professed air. Fuel adulteration in least developed countries like Nepal is a malpractice that can have serious economic and health related implications. The objective of this paper is to estimate the monetary cost of acute respiratory illnesses ARI morbidity, mortality and calculate year of life lost [YOLL], (productivity loss, and human capital loss). Increase in emission in Kathmandu valley that seriously pollutes the atmosphere and further causes the diseases like asthma, cancer, respiratory illness, cardio vascular and air pollution damages human health seriously. It seems that increased death casualties are caused by air-burn diseases, and by the rapidly rising degree of air pollution particularly (PM10) in Kathmandu valley. By applying OLS method this paper has evaluated the impact of tail pipe emission in human health in Kathmandu valley and central development region of Nepal. The findings indicate that there is high health cost of the polluted air in Kathmandu valley. This result should be taken as a frightening indication of the impact of polluted air on the health of the people of Kathmandu. The increasing PM10 content found in the air of Kathmandu valley alone would be counted as a factor causing pneumonia among the peoples to a considerable extent. Key words: Air pollution; PM10; Health impact; Monetary cost; Mortality; Morbidity; YOLL Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page : 1-20